Hydrodynamic cavitation kills prostate cells and ablates benign prostatic hyperplasia tissue. (November 2013) - Itah, Zeynep; Oral, Ozlem; Perk, Osman Yavuz; Sesen, Muhsincan; Demir, Ebru; Erbil, Secil; Dogan-Ekici, A Isin; Ekici, Sinan; Kosar, Ali; Gozuacik, Devrim
Hydrodynamic cavitation is a physical phenomenon characterized by vaporization and bubble formation in liquids under low local pressures, and their implosion following their release to a higher pressure environment. Collapse of the bubbles releases high energy and may cause damage to exposed surfaces. We recently designed a set-up to exploit the destructive nature of hydrodynamic cavitation for biomedical purposes. We have previously shown that hydrodynamic cavitation could kill leukemia cells and erode kidney stones. In this study, we analyzed the effects of cavitation on prostate cells and benign prostatic hyperplasia (BPH) tissue. We showed that hydrodynamic cavitation could kill prostate cells in a pressure- and time-dependent manner. Cavitation did not lead to programmed cell death, i.e. classical apoptosis or autophagy activation. Following the application of cavitation, we observed no prominent DNA damage and cells did not arrest in the cell cycle. Hence, we concluded that cavitation forces directly damaged the cells, leading to their pulverization. Upon application to BPH tissues from patients, cavitation could lead to a significant level of tissue destruction. Therefore similar to ultrasonic cavitation, we propose that hydrodynamic cavitation has the potential to be exploited and developed as an approach for the ablation of aberrant pathological tissues, including BPH.